APPLICATION OF COLLOCATION IN AL-QUR`AN - Imroatul Fatihah (EL-IBTIKAR: Jurnal Pendidikan Bahasa Arab, 2017)
AbstractThe word collocation and collocation of sentence structure both have a role in giving meaning. Word will not produce meaning without any relation with other words. The word relation is a combination commonly used by native speakers. Native language speakers will naturally combine familiar words using trained intuition. Where accuracy in combining word pairs is called by linguists as collocation.This study concludes that collocation at the level of the word in the Qur'an produces a polysemic meaning. This means that every word in the Qur'an has a lot of meaning that requires a relationship between words with a harmonious combination. Because of each word has a precision in the use of a sentence. Example word الحمد, this word is synonymous with the word المدح and also the word الثناء. These three words have the meaning of praise and appreciation of a beauty, pleasure or other that is immaterial. As an expression of praise to Allah the exact combination of three words is using the word الحمد. The word الحمد also contains meaning, الشكر but the use of the word الحمد is only used to express gratitude to God, while to express gratitude to the creature by using the word شكر.Keywords: Collocation, Linguistic, Al-Qur’an